Why Presidents Fail: White House Decision Making from Eisenhower to Bush II - Pious, Richard M. (Rowman & Littlefield Publishers, 2008)
Presidents are surrounded by political strategists and White House counsel who presumably know enough to avoid making the same mistakes as their predecessors. Why, then, do the same kinds of presidential failures occur over and over again? Why Presidents Fail answers this question by examining presidential fiascos, quagmires, and risky business-the kind of failure that led President Kennedy to groan after the Bay of Pigs invasion, 'How could I have been so stupid?' In this book, Richard M. Pious looks at nine cases that have become defining events in presidencies from Dwight D. Eisenhower and the U-2 Flights to George W. Bush and Iraqi WMDs. He uses these cases to draw generalizations about presidential power, authority, rationality, and legitimacy. And he raises questions about the limits of presidential decision-making, many of which fly in the face of the conventional wisdom about the modern presidency.